What are the costs associated with nausea and vomiting in pregnancy and hyperemesis gravidarum? A systematic review - Antonia Gazal; Vanessa Scarf; Caitlin Kay-Smith; Beata Gidaszewski; Seng Chua; Kate Levett (BMC Pregnancy and Childbirth)
Abstract Background Nausea and vomiting of pregnancy (NVP) and its more severe form, hyperemesis gravidarum (HG) are common and debilitating causes of maternal morbidity. However, evidence regarding the economic burden is limited. Aim To identify studies focusing on the costs associated with NVP and HG, to estimate the economic burden of NVP and HG. Methods A literature search was conducted in 2023 using five electronic databases. Articles were appraised using both the Larg and Moss checklist and the CASP tool for Economic Analyses. Included studies reported the cost of illness, economic burden, or health care expenditures related to NVP and/or HG. A narrative synthesis was performed. Costs were adjusted for inflation and currency differences, presented in 2023 US dollars ($USD). Results Seven studies were included from 652 studies identified. The studies were methodologically and clinically heterogenous and lacked consistent reported outcome measures. All identified a significant economic burden of NVP and HG, including substantial annual and direct per patient costs, as well as indirect costs to the patient. Costs increased with severity of disease, and outpatient or day stay units were more cost-effective models of care including via reduction of disease severity. Conclusions Our findings indicate the significant economic burden associated with NVP and HG. Original studies differed in methodology and outcomes measured; however substantial cost savings were demonstrated through targeted models of care. As there is little information about the economic burden of HG and NVP, further studies are required, with agreed outcome data, to inform policy and practice.